Oral manifestations of primary hyperoxaluria in adult patient (Research, Society and Development, 2021)
Primary hyperoxaluria (PH) is a rare disease, autosomal recessive inheritance disorder. This disease leads to overproduction of oxalates, and the excretation inability results in deposition of calcium oxalate crystals in almost all tissues presenting the oxalosis condition. The treatment is a combined liver and kidney transplantation (CLKT), which enables a better patient survival. Due to this survival, the patients had could present a several oral manifestations such as periodontal disease, root resorption, dental pain and increased tooth mobility. However, currently, there is a lack of information in the literature about all oral manifestations that this patient can present. Beside this, there are doubt and challenge about treatments to this patient in these different oral manifestations. The present study aims to report a case of a patient with hyperoxaluria type I with oxalosis oral manifestations.